2021
DOI: 10.1021/acsami.0c19736
|View full text |Cite
|
Sign up to set email alerts
|

Normal Load and Counter Body Size Influence the Initiation of Microstructural Discontinuities in Copper during Sliding

Abstract: Near the interface of two contacting metallic bodies in relative motion, the microstructure changes. This modified microstructure leads to changes in material properties and thereby influences the tribological behavior of the entire contact. Tribological properties such as the friction coefficient and wear rate are controlled by the microstructure, while the elementary mechanisms for microstructural changes are not sufficiently understood. In this paper, the influence of the normal load and the size of the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
2
8
1
Order By: Relevance
“…the dislocation free zone) due to the strong stress concentration, which drives dislocations to leave the materials from crack surfaces (Huang and Li, 2004) , at the latter position. Hence the peak GND density (manifesting itself as lattice rotation) is observed with an offset distance from the crack tip, which is similar to the discussion in the microstructure change under tribological constraint (Chen et al, 2018b;Ruebeling et al, 2021). Besides, an asymptotic analysis (Le and Tran, 2016) The stored energy density G proposed in (Wan et al, 2014) is given as:…”
Section: Edge Crack Under Mode I Loadingsupporting
confidence: 66%
“…the dislocation free zone) due to the strong stress concentration, which drives dislocations to leave the materials from crack surfaces (Huang and Li, 2004) , at the latter position. Hence the peak GND density (manifesting itself as lattice rotation) is observed with an offset distance from the crack tip, which is similar to the discussion in the microstructure change under tribological constraint (Chen et al, 2018b;Ruebeling et al, 2021). Besides, an asymptotic analysis (Le and Tran, 2016) The stored energy density G proposed in (Wan et al, 2014) is given as:…”
Section: Edge Crack Under Mode I Loadingsupporting
confidence: 66%
“…TEM foils were prepared by thinning with the Ga + -ion beam after covering the area of interest with electron-and ion-beam-assisted Pt deposition. See Greiner et al [25] and Ruebeling et al [26] for detailed method and parameter descriptions.…”
Section: Methodsmentioning
confidence: 99%
“…It was recently observed that this dislocation self-organization is also the location where a localized simple shear of the subsurface material occurs in the sliding direction [24]. Moreover, it was found to be present for a wide range of experimental parameters, such as the counterbody size and normal load [26], as well as for various sliding speeds [29], meaning its occurrence warrants a closer look. It is believed that the DTL is the demarcation line between the development of a nanocrystalline layer and the bulk material underneath as sliding progresses.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent experiments on face-canter-cubic (FCC) samples have observed an abrupt and highly localized microstructure change (termed as "dislocation traceline" (DTL)) [28,29] at ~100 nm depth from the contact during one-stroke sliding. This microstructural change eventually leads to recrystallization of the single crystal in subsequent cyclic loadings when the material is more heavily loaded [30]. Approaches based on continuum assumptions [31] to identify microstructural changes, albeit providing good qualitative insight as to where such activity may take place, are hardly able to fully explain the mechanistic drivers for the formation of the dislocation traceline and the evolution of the discrete features associated with microstructural evolution.…”
Section: Introductionmentioning
confidence: 99%